A selected probiotic strain of Lactobacillus fermentum CM33 isolated from breast-fed infants as a potential source of β-galactosidase for prebiotic oligosaccharide synthesis - Sriphannam W. (2014)
Lactic acid bacteria from healthy breast-fed infants were isolated and screened for β-galactosidase production in MRS broth. Among 49 isolates that exhibited the yellow clear zone on MRS agar supplemented with bromocresol blue, the isolate CM33 was selected as being the highest β-galactosidase producer and was identified as Lactobacillus fermentum based on its morphological characteristics and 16S rDNA nucleotide sequence. L. fermentum CM33 exhibited a good survival rate under the simulated stomach passage model, comparable to known probiotic strains L. gallinarum JCM2011 and L. agilis JCM1187. L. fermentum CM33 was antagonistic to pathogenic bacteria Listeria monocytogenes, Escherichia coli 0157:H7, Salmonella typhi, and Salmonella enteriditis, using the well diffusion method. In addition, the selected lactobacilli exhibited a high growth rate when cultivated in modified MRS containing commercial galactooligosaccharide (GOS) as a sole carbon source, as well as in glucose. A preliminary study on the enzymatic synthesis of oligosaccharide using crude β-galactosidase revealed the capability for oligosaccharide synthesis by the transgalactosylation activity. © 2012 The Microbiological Society of Korea and Springer-Verlag Berlin Heidelberg.